1999
DOI: 10.1083/jcb.145.3.515
|View full text |Cite|
|
Sign up to set email alerts
|

Hyphal Death during Colony Development in Streptomyces antibioticus: Morphological Evidence for the Existence of a Process of Cell Deletion in a Multicellular Prokaryote

Abstract: During the life cycle of the streptomycetes, large numbers of hyphae die; the surviving ones undergo cellular differentiation and appear as chains of spores in the mature colony. Here we report that the hyphae of Streptomyces antibioticus die through an orderly process of internal cell dismantling that permits the doomed hyphae to be eliminated with minimum disruption of the colony architecture. Morphological and biochemical approaches revealed progressive disorganization of the nucleoid substructure, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 51 publications
2
85
0
Order By: Relevance
“…Most cells in substrate mycelium die during aerial mycelium formation, because the aerial mycelium reuses material first assimilated into the substrate mycelium (20,31). A detailed morphological study on the colony development of Streptomyces antibioticus (5,21) has shown that, in substrate mycelium, the nucleoid structure is disorganized, followed by progressive degradation of cytoplasmic contents and distortion of the hyphal shape. In addition, hyphal death occurs at a specific region and time; this process is known as programmed cell death.…”
Section: Vol 184 2002 a Metalloprotease Gene Controlled By A-factormentioning
confidence: 99%
See 1 more Smart Citation
“…Most cells in substrate mycelium die during aerial mycelium formation, because the aerial mycelium reuses material first assimilated into the substrate mycelium (20,31). A detailed morphological study on the colony development of Streptomyces antibioticus (5,21) has shown that, in substrate mycelium, the nucleoid structure is disorganized, followed by progressive degradation of cytoplasmic contents and distortion of the hyphal shape. In addition, hyphal death occurs at a specific region and time; this process is known as programmed cell death.…”
Section: Vol 184 2002 a Metalloprotease Gene Controlled By A-factormentioning
confidence: 99%
“…Subsequently, aerial hyphae emerge by reuse of material assimilated into the substrate mycelium, such as DNA, proteins, and storage compounds. Many cells in substrate hyphae thus lyse and die (5,21,31). At this stage of development, therefore, enzymes for the degradation of these substances, such as proteases, nucleases, lipases, and glucanases, are presumably required.…”
mentioning
confidence: 99%
“…In Myxobacteria, Streptomyces and Bacilli, nutrient shortage induces the terminal differentiation, followed by the death, of a part of the cells from the colony; these terminally differentiated cells helping the other part of the cells from the colony to differentiate into long-lived non-cycling and highly resistant spores. 173,184,186 Although environmental changes represent the initial and necessary trigger for the complex set of modifications that will lead to this process of alternate and complementary differentiation, the environmental signals by themselves are not sufficient: an additional step of intercellular signaling is required, that will lead to a coordinated set of changes in gene expression. 155,186 In Myxococcus xanthus, for example, the decision upon nutrient shortage to either continue to grow (at a reduced rate) or to trigger a developmental program that will lead to programmed cell death and sporulation, depends on two limiting factors: the density of cells in the bacterial colony, and the density of individual cells, in that colony, that will respond to the environmental change.…”
Section: On Paradigms`anomalies' And`retrorecognition'mentioning
confidence: 99%
“…These mycelial bacteria follow a complex developmental program that includes two types of interrelated differentiation i.e., (i) a morphological differentiation where aerial hyphae, whose tips ends will differentiate into spores, arise from the substrate (vegetative) mycelium and (ii) a physiological/metabolic differentiation characterized by the production of the so-called secondary metabolites. The onset of both types of differentiation correlates with one of the most sophisticated examples of a programmed cell death (PCD) process in prokaryotes (Granozzi et al 1990;Miguelez et al 1999). The latest model suggests two rounds of PCD during Streptomyces life cycle (Manteca et al 2011).…”
Section: Introductionmentioning
confidence: 99%